High Soil Potassium Levels Do Not Increase Leaf Potassium Concentration in Rabbiteye or Southern Highbush Blueberry - Natalia Espinoza; Jason Lessl; Zilfina Rubio Ames (HortScience)
In the coastal plains of Georgia, soils are sandy with low pH, low cation exchange capacity (CEC), and a high rate of K leaching. To manage crop nutrition effectively and preserve soil physicochemical properties, it is essential to adjust fertilizer applications to the physiological demands of the plants. This research project aimed to determine the relationship between K in the soil and leaves and its impact on yield of rabbiteye blueberry (Vaccinium virgatum Aiton) and southern highbush blueberry (a complex hybrid based largely on Vaccinium corymbosum L. and Vaccinium darrowii Camp.). Soil and leaf samples were collected on four commercial farms, including 384 soil samples and 252 leaf samples from Apr to Nov 2022 and 2023. Our results indicated no correlation between soil and leaf K concentrations. Still, soil K was positively correlated with P and Mn in the soil, and leaf K was positively correlated with P, Mn, S, and Na in the leaves. The highest-yielding farm did not have higher soil K concentrations than the other farms, but it did have plants with the highest level of K in the leaves. The results of this study show that soil K alone may not reliably indicate plant K or yield in blueberries. Leaf nutrient analysis is critical for effective nutrient management and better crop production.